The restriction for tan^-1x tan−1x is (-pi/2,pi/2)(−π2,π2) but (11pi)/1011π10 is in quadrant III. Since tangent is positive in quadrant III our answer will be in the positive quadrant from the restriction which is quadrant I. So let's find the reference angle which is (11pi)/10-pi=pi/1011π10−π=π10. Then since the reference angle equals the angle thetaθ in quadrant one our argument in quadrant one is also pi/10π10. Now apply the property f^-1(f(x))=xf−1(f(x))=x
Therefore,
tan^-1(tan((11pi)/10))=tan^-1(tan((pi)/10))=pi/10tan−1(tan(11π10))=tan−1(tan(π10))=π10